Implementasi Pembelajaran Bahasa Arab melalui Pendekatan Saintifik di Kelas 1 MI Ar-Rahmah Jabung Kabupaten Malang - Amang Fathurrohman; Hasyim (Universitas Yudharta Pasuruan, 2020)
Madrasah Ibtidaiyah Ar-Rahmah Malang is a primary level educational institution in Jabung District of Malang Regency. Since Class 1, students have been introduced to Arabic language lessons using a scientific approach. Through qualitative methods, the results of this study indicate that the implementation of Arabic learning using a scientific approach has been carried out by Madrasah Ibtidaiyah Ar-Rahmah teachers. Various methods are used so that the scientific approach can be achieved properly. However, because they are still in class 1 Madrasah Ibtidaiyah, the emphasis on Arabic is still directed to memorize mufrodat related to everyday themes. So the scientific approach is still not optimal to be implemented in grade 1 students of Madrasah Ibtidaiyah Ar-Rahmah Jabung Malang.